Preface: The Linkages between Local Entrepreneurship and Regional Economic Development - Sloboda, Brian W. (European Scientific Journal, ESJ, 2020)
A discussion of the linkages between local entrepreneurship and regional economic development provides an intriguing starting point for a wider reflection on the role of existing policies as well as emerging practices that promote regional economic development. Existing literature investigates the role of entrepreneurship and regional economic development. Increasingly, this has been conceptualized in terms of entrepreneurial ecosystems. However, the current literature is fragmented and too often based on problematic assumptions. There are major disconnects between scholars, policymakers, and practitioners. For example, a fast-growing phenomenon is the rise of ecosystem building and ecosystem builders as championed by the Ewing Marion Kauffman Foundation and its ESHIP initiative. Little research has addressed this and presents a significant opportunity for innovative, rigorous research that will influence policy and practice. This editorial introduction provides a summary of the contributions included in the special issue on the linkages between local entrepreneurship and regional economic development. These articles focus on the various application of the linkages between local entrepreneurship and regional economic development. The editorial concludes by providing some direction for future research.